Strengthening the social dimension of the Lisbon strategy - Zeitlin, Jonathan (Madison, 2007)
"The author introduces a discussion of how to strengthen the social dimension of the Lisbon Strategy by focusing on the question of how best to implement the conclusion of the spring 2007 European Council that “the common social objectives of Member States should be better taken into account within the Lisbon Agenda.”